Reformulation of Islamic Religious Education Curriculum for Adaptive and Inclusive Education - Juliani; Reni Purnama Sari; Nova Indrianti; Fadhillah Syahfitri; Najla Fadhillah (Yayasan Zia Salsabila, 2025)
Islamic Religious Education (PAI) in Indonesia plays an important role in shaping the character and identity of the younger generation. However, along with the rapid development of globalization, technological advances, and social diversity, the current PAI curriculum is considered unable to answer these challenges effectively. Therefore, an adaptive and inclusive PAI curriculum reformulation is needed to meet the needs of education that is relevant to the times. This study aims to explore and analyze how the reformulation of the PAI curriculum that is responsive to changes in the times and the diversity of students can improve the quality of religious education in Indonesia. Using a qualitative approach and literature study method, this study explores the concepts and principles of curriculum reformulation that focus on the integration of the values of moderation, tolerance, and character in Islamic religious education. The results of the study indicate that the reformulation of the PAI curriculum needs to involve a more inclusive approach, pay attention to different learning styles, and utilize technology to make learning more interactive and interesting. In addition, the PAI curriculum must prioritize character education that not only teaches religious teachings, but also instils positive attitudes and behaviours in everyday life. This reformulation must also involve active participation from various parties, such as educators, parents, and the community, to produce a more comprehensive curriculum that is in accordance with students' needs. Thus, an adaptive and inclusive Islamic Religious Education curriculum is expected to be able to create a young generation that is not only academically intelligent, but also has good morals, has relevant life skills, and is able to face global challenges with a moderate, tolerant attitude, and respects diversity.